THE PRINCIPLE OF PROPORTIONALITY ON DIGITAL BUSINESS AGREEMENTS: BETWEEN MITIGATION AND ORIENTATION - Miftah Arifin; Zaenal Arifin; Mac Thi Hoai Thuong (Faculty of Law, Universitas Lampung, 2023)
The Agreement as part of civil law is one of everyday life's most frequently performed actions. This study aims to anticipate the development of digital agreements by contextualizing the provisions of laws and regulations regarding agreements. This research is normative legal research that uses statutory and conceptual approaches. The results of the study confirm that efforts to mitigate digital agreements following contract law are by still referring to Article 1320 of the Civil Code by prioritizing four orientations to minimize risks in digital agreements. First, the preventive orientation by looking at the parties who are invited to enter into agreements. Second, the prudence and proportionality in reading the provisions in digital agreements. Third, the prudence and proportionality of digital agreements by including names as well as identities that can be contacted and can be accounted for by the parties. Fourth, prudence and proportionality in determining the object of the agreement. Furthermore, the orientation of digital agreements based on the principle of proportionality based on philosophical, sociological, and juridical aspects requires specific arrangements, particularly regarding the minimum requirements for implementing digital agreements. That is because the unique characteristics of digital agreements need special arrangements regarding the terms of the validity of digital agreements, which in general still refer to Article 1320 of the Civil Code.